Imago Dei dan Transhumanisme: Antara Tantangan atau Paradigma Baru Bagi Teologi Kristen - Sitorus, Dasvan Abdi Natanel; Marpaung, Frans Best Soma (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2025)
This article discusses the relationship between Imago Dei and Transhumanism in the context of Christian theology, presenting research focused on critical analysis of relevant literature and theological interpretation of this complex relationship. The research method employed is descriptive qualitative with a literature review approach. Through the identification and analysis of contemporary theological literature, the study aims to understand the Christian theological perspectives on the concept of Imago Dei and its interaction with the phenomenon of transhumanism. The ethical and theological implications of this relationship are discussed by considering the optimistic vision of technology in achieving greater good and the framework of Imago Dei in addressing human limitations and dependence. The findings of this research are expected to provide a deep understanding of the Christian theological response to transhumanism and whether transhumanism is perceived as a challenge or a new paradigm within the framework of Imago Dei. In conclusion, Christian theology needs to support an optimistic view of technology while considering the ethical and theological dimensions of the changes proposed by transhumanism.